2010
DOI: 10.1177/1479972310378311
|View full text |Cite
|
Sign up to set email alerts
|

The endurance shuttle walk test: An alternative to the six-minute walk test for the assessment of ambulatory oxygen

Abstract: UK guidelines for domiciliary oxygen have suggested the six-minute walk test or shuttle walk tests as suitable functional measures for the clinical assessment of ambulatory oxygen (AO). To date, there is limited evidence that would support the use of shuttle walk tests as assessment tools for AO. The endurance shuttle walk test (ESWT) is used increasingly as an assessment tool within pulmonary rehabilitation (PR) but its potential as an investigative test for AO has not been explored. Using the same test for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…2). However, the shuttle tests may be more sensitive to the effects of common interventions, including bronchodilators [106,233,234]. The externally paced nature of the ISWT and ESWT may be an advantage in circumstances where methodological variation is a concern (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2). However, the shuttle tests may be more sensitive to the effects of common interventions, including bronchodilators [106,233,234]. The externally paced nature of the ISWT and ESWT may be an advantage in circumstances where methodological variation is a concern (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additional measures can be recorded. Three studies demonstrated the potential for the use of SpO 2 to record exertional desaturation during ESWT, either breathing air or for assessment of ambulatory oxygen [219,233,242]. One study reported greater desaturation with ESWT compared with 6MWT [233].…”
Section: Measurements and Reporting For Eswtmentioning
confidence: 99%
See 2 more Smart Citations
“…The randomness of this variability suggests that it was not related to a learning effect, as confirmed by the Bland-Altman plot. The issue about intraindividual variability in exercise performance was previously discussed for the ESWT [12,[19][20][21], but also for constant work-rate cycling exercise [22]. REVILL et al [21] reported greater variability in ESWT performance with longer endurance time.…”
Section: Reproducibility Of Eswt Performancementioning
confidence: 99%